If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10m + 7m = 0 Combine like terms: -10m + 7m = -3m -3m = 0 Solving -3m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-3'. m = 0 Simplifying m = 0
| 3x-8=2.5 | | -4y^2+16y-15=0 | | 20s+10l=500 | | 9^2*72-(6^2/2)^3 | | w(-2)=x^2+3-2x | | 4-3x=-3x+4-2x | | 15s+4l=305 | | 30x^2+16x-161=0 | | 2x^2+11x=-15 | | 4-3x=3x+-4-2x | | 7+y=-9 | | 4-3x=3x+6-2x | | -4(2x+5)=6x | | 32=2x-8 | | R=r/l | | h(x)=3x+4 | | 4(r-2)=2(r+8) | | 4x-4=8+a | | 7x-7-5x=4 | | 124/2 | | 5y-8y+7=22 | | 27=3v-12 | | 5y-8y+7=23 | | -2x/150 | | 2=lx+5l+2 | | 10n+12=72 | | m+3=11+3m | | -21+4m=-5 | | 6x-3x-10=11 | | -6+m=-22 | | 2(12)+31+12n+11=180 | | -1a+1135=4a+105 |